'Christian civilisation', 'modern secularisation', and the revolutionary re-imagination of British modernity, 1954-1965. Issue 4 (1st October 2020) - Brewitt-Taylor, Sam
ABSTRACT: This essay argues that essentialist models of modernity are always ideological, and that Britain's dominant ideology of modernity was transformed from the mid-1950s, with revolutionary consequences for British Christianity and secularisation. Before the mid-1950s Britain's predominant 'civilisation' ideology portrayed Christianity as more advanced than secularity. The mid-1950s global crisis, however, created widespread belief in a radical break between 'tradition' and 'the modern world'. This perception rapidly legitimated the further belief, promoted by radical Christians, that 'the modern world' is inherently 'secular'. Once accepted by the national media, the ideological belief that modernity is secular made possible the 1960s 'secular revolution'.